Culture and Attention: Future Directions to Expand Research Beyond the Geographical Regions of WEIRD Cultures - Masuda, Takahiko; Batdorj, Batgerel; Senzaki, Sawa (Frontiers in Psychology, 2020)
For the past 30 years, the field of cultural psychology has succeeded in demonstrating the diversity of human cognition. Henrick, Heine, and Norenzayan (2010) highlighted the necessity for broadening the range of regions for cross-cultural investigation in their seminal paper “The weirdest people in the world”. They criticize the current psychological framework for relying dominantly on American Undergraduate students for their participant database, and state that there is a risk associated with investigating human nature through focusing solely on a unique population. However, there are still only a limited number of studies that have succeeded in extending their geographical regions of research outside of G7 (Canada, France, Germany, Italy, Japan, UK, and USA) and G20 countries (Argentina, Australia, Brasil, China, India, Indonesia, Mexico, Russia, Saudi Arabia, South Africa, South Korea, Turley, EU countries, and the above G7 countries). In order to fully examine the issue of culture and cognition, the field of psychology must extend their research globally. In this paper, we will discuss a brief history of cross-cultural research in the 1960’s which can be seen as the beginning of addressing the above concerns, and review contemporary empirical studies which took over the 1960’s predecessors’ mission. Here we address three strengths of expanding geographical regions to advance cultural psychology. In the second half of the paper, we will introduce our preliminary study conducted in Mongolia as a case sample study to demonstrate a way of administering cultural psychological research outside of the existing research field. We will then discuss implications of this line of research, and provide tips on how to open a new research site.